Genetyka tekstów dawnych, czyli nowe perspektywy w badaniu starych problemów dawnej kultury rękopisu - Cybulski, Łukasz (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
Textual genetics originated as a field of modern literary research and for decades its applicability to the study of early modern manuscripts was outright denied. Therefore, I will first present the issues of genetic research in relation to 16th- and 17th-century writings. I will also discuss the problems arising from the specific nature of early modern textual documentation, such as the understanding of the phenomenon of authorship and textual fluidity, or the specific nature of genetic documents. The intended goal of this analysis is to show that the recontextualization of the tools of genetic criticism not only facilitates the study of old manuscripts, but also constitutes an important complement to traditional philological practices. Furthermore, in addition to summarizing the preliminary stage of my own research in this field, I will indicate potential objectives for this type of study, and will discuss how the new perspective may redefine our perceptions of early modern manuscript culture.